IL-33/ST2 Axis in Organ Fibrosis - Kotsiou, Ourania S.; Gourgoulianis, Konstantinos I.; Zarogiannis, Sotirios G. (Frontiers in Immunology, 2018)
Interleukin 33 (IL-33) is highly expressed in barrier sites, acting via the suppression of tumorigenicity 2 receptor (ST2). IL-33/ST2 axis has long been known to play a pivotal role in immunity and cell homeostasis by promoting wound healing and tissue repair. However, it is also involved in the loss of balance between extensive inflammation and tissue regeneration lead to remodeling, the hallmark of fibrosis. The aim of the current review is to critically evaluate the available evidence regarding the role of the IL-33/ST2 axis in organ fibrosis. The role of the axis in tissue remodeling is better understood considering its crucial role reported in organ development and regeneration. Generally, the IL-33/ST2 signaling pathway has mainly anti-inflammatory/anti-proliferative effects; however, chronic tissue injury is responsible for pro-fibrogenetic responses. Regarding pulmonary fibrosis mature IL-33 enhances pro-fibrogenic type 2 cytokine production in an ST2- and macrophage-dependent manner, while full-length IL-33 is also implicated in the pulmonary fibrotic process in an ST2-independent, Th2-independent fashion. In liver fibrosis, evidence indicate that when acute and massive liver damage occurs, the release of IL-33 might act as an activator of tissue-protective mechanisms, while in cases of chronic injury IL-33 plays the role of a hepatic fibrotic factor. IL-33 signaling has also been involved in the pathogenesis of acute and chronic pancreatitis. Moreover, IL-33 could be used as an early marker for ulcer-associated activated fibroblasts and myofibroblast trans-differentiation; thus one cannot rule out its potential role in inflammatory bowel disease-associated fibrosis. Similarly, the upregulation of the IL-33/ST2 axismay contribute to tubular cell injury and fibrosis via epithelial to mesenchymal transition of various cell types in the kidneys. Of note, IL-33 exerts a cardioprotective role via ST2 signaling, while soluble ST2 has been demonstrated as a marker of myocardial fibrosis. Finally, IL-33 is a crucial cytokine in skin pathology responsible for abnormal fibroblast proliferation, leukocyte infiltration and morphologic differentiation of human endothelial cells. Overall, emerging data support a novel contribution of the IL-33/ST2 pathway in tissue fibrosis and highlight the significant role of the Th2 pattern of immune response in the pathophysiology of organ fibrosis.